2020
DOI: 10.3390/sym12101681
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Visual Similarity-Based Phishing Websites Detection

Abstract: This work proposes an intelligent visual technique for detecting phishing websites. The phishing websites are classified into three categories: very similar, local similar, and non-imitating. For cases of ‘very similar’, this study uses the wavelet Hashing (wHash) mechanism with a color histogram to evaluate the similarity. In cases of ‘local similarity’, this study uses the Scale-Invariant Feature Transform (SIFT) technique to evaluate the similarity. This work concerns ‘very similar’ and ‘local similar’ case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…. 18. Initial experiments showed that the best results were obtained with the 80/20 split, which was used for the remaining combinations of features (m = 6. .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…. 18. Initial experiments showed that the best results were obtained with the 80/20 split, which was used for the remaining combinations of features (m = 6. .…”
Section: Methodsmentioning
confidence: 99%
“…The machine learning approach is most common for the analysis of website content and address. Content analysis is based on the features related to HTML (Hyper Text Markup Language) [14][15][16], body text [17], images [17][18][19][20], domain registration information [15,21] and styles [22]. The URL analysis [21,[23][24][25][26][27] is usually based on the features related to the length of the full URL, the domain name, the directory, the types of symbols, the protocol, the number of symbols, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Page similarity has been extensively investigated in the literature to detect phishing web pages (see, e.g., [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58]). In fact, as already pointed out, web pages are made in a way to look very similar or identical to their legitimate counterparts, thus their similarity is a good indicator of a phishing attack.…”
Section: Page Similarity-based Detection Methodsmentioning
confidence: 99%
“…Chen et al 6 proposed a method to detect phishing websites. The websites are first classified based on the level of similarity and separate methods are applied to each category.…”
Section: Literature Reviewmentioning
confidence: 99%